Buen Vivir, Sumak Kawsay, 'Good Living': An Introduction and Overview (Alternautas, 2014)
This overview and introduction to Buen Vivir and/or Sumak Kawsay refers to the context and discussion in Ecuador. It differentiates between Buen Vivir and Sumak Kawsay as well as between (at least) three main types of this vast field of discourses and practices: (1) a state-led program for the 'socialism of the 21st century"; (2) a post-modern utopian and intellectual project, drawing on indigenous Andean values; and (3) an (essentializing) 'indigenist' form of living and thinking that adds spiritual ontological dimensions, based on individually and collectively acquiring a practice of all-connected consciousness.